STUDI AKUNTABILITAS PUBLIK PADA BIDANG KEPENDUDUKAN DI KANTOR KECAMATAN ANGGANA KABUPATEN KUTAI KARTANEGARA - Rozali, Faridz (PREDIKSI, 2015)
ABSTRACTÂ The purpose of this study is to analyze the public accountability in the field of population and to analyze what are the factors inhibiting the public accountability in the field of population in Kutai Kartanegara District Office Anggana. Key informants in this study is the Head of Governance and employees in the field of population Kutai Kartanegara District Office Anggana . And informants in this study were community Anggana District of Kutai Kertanegara, the people here are people who need public services, especially in the field of population in Kutai Kertanegara District Office Anggana . This research is descriptive and analytical penilitian which consists of three series that occur simultaneously, namely: data reduction, data presentation, and inference/ verification. The results of the analysis were that accountability will be influenced by both the infrastructure supporting work - administrative and operational work field. District government policy also has a direct influence on working implementation at the district level as devolution wemarsidiang and LPJK rules.